MODELING OF GROUND SURFACE DEFORMATIONS DURING DRAINAGE OF SOIL MASSIFS - Кузло, Микола (SWorldJournal, 2024)
The mathematical model for predicting deformations of water-saturated soil massifs during their drainage has been developed. The vertical displacements of the ground surface during the construction of drainage channels on the existing hydromelioration sys